Scanning-Raman-microscopy for the statistical analysis of covalently functionalized graphene - Englert, Jan; Vecera, Philipp; Knirsch, Kathrin; Schäfer, Ricarda; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Acs Nano, 2013)
We report on the introduction of a systematic method for the quantitative and reliable characterization of covalently functionalized graphene based on Scanning-Raman-Microscopy (SRM). This allows for recording and analyzing several thousands of Raman spectra per sample and straightforward display of various Raman properties and their correlations with each other in histograms or coded 2D-plots. In this way, information about the functionalization efficiency of a given reaction, the reproducibility of the statistical analysis, and the sample homogeneity can be easily deduced. Based on geometric considerations, we were also able to provide, for the first time, a correlation between the mean defect distance of densely packed point defects and the Raman I/I ratio directly obtained from the statistical analysis. This proved to be the prerequisite for determining the degree of functionalization, termed θ. As model compounds, we have studied a series of arylated graphenes (GPh) for which we have developed new synthetic procedures. Both graphite and graphene grown by chemical vapor deposition (CVD) were used as starting materials. The best route toward GPh consisted of the initial reduction of graphite with a Na/K alloy in 1,2-dimethoxyethane (DME) as it yields the highest overall homogeneity of products reflected in the widths of the Raman I /I histograms. The Raman results correlate nicely with parallel thermogravimetric analysis (TGA) coupled with mass spectrometry (MS) studies. © 2013 American Chemical Society.